Figure skating musculoskeletal injury: evidence across disciplines, mechanisms, and future directions - Madsen, A.; Alfonso, K.; Vincent, H. K. (Current Sports Medicine Reports, 2024)
This review provides a synopsis of current injury patterns, potential mechanisms, and off-ice exercise prevention considerations as the sport of figure skating evolves. The lifetime prevalence of injury for all skaters is estimated to be 79.5%, with the most common sites being spine and lower extremity. Singles skaters more often develop chronic injuries compared to acute (68.9% vs 31.1%), whereas non-singles skaters more often experience acute injuries. Lower limb stress fracture prevalence ranges from 10% to 21.4% across disciplines. Emerging contributors include training volume, technical difficulty and repetition of complex elements (multirotational jumps, lifts, holds), extreme ranges of movement about the spine and hip, age and experience level, and functional capacity (dynamic strength, flexibility, balance, and neuromotor control). Prevention programs in competitive figure skaters may include monitoring of training volumes, emphasis on technique, appropriate boot fit, and strength and conditioning content to prepare for increasing neuromotor, balance, and power demands of the sport.